Frequency of Subclinical Hypothyroidism in Patients with First-Trimester Pregnancy Loss - Saleha Hassan; Rabiya Akbar; Uzma Urooj; Sadaf Zohra; Nusrat Noor (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To determine the frequency of subclinical Hypothyroidism in women with first-trimester pregnancy loss.